Analysis of Information System Quality on User Satisfaction of the Regional Financial Management Information System (SIPKD) Using the Delone & Mclean Model in the East Jakarta Administration Mayor's Government - Ramadhan, Muhammad Ilham; Rizal, Erian (ISB Atma Luhur, 2025)
This study aims to evaluate the effect of information system quality on the level of user satisfaction of the Regional Financial Management Information System (SIPKD), with reference to the DeLone and McLean Model framework. The subject of this research is the State Civil Apparatus (ASN) who works within the East Jakarta Administrative City Government. The DeLone and McLean model is used as a basis for assessing how the quality of information, systems, and services affects usage intensity, user satisfaction, and individual performance. The approach used was quantitative, with data collection through distributing questionnaires to 100 respondents. Data analysis was conducted using the Structural Equation Modeling (SEM) method with the help of Partial Least Squares (SmartPLS) software. The results of the analysis show that information quality significantly affects user satisfaction, but does not show a significant effect on usage intensity. Meanwhile, system quality and service quality are proven to have a significant effect on usage intensity, but not on user satisfaction. Intensity of use has a positive and significant impact both on user satisfaction and on improving individual performance. In addition, user satisfaction is also proven to have a significant effect on individual performance.